The Effect of Omnichannel Strategy and Personal Selling on Customer Experience Quality Among Small and Medium Enterprise Consumers in Cirebon City - Moh. A’ip Saepul Rohman; Siska Ernawati Fatimah (Interdisciplinary Social Studies, 2026)
This study is motivated by the rapid transformation of consumer behavior in the digital era, which encourages small and medium enterprises (SMEs) to adopt omnichannel strategies and improve personal selling quality in order to create better customer experiences. The increasing use of digital platforms, social commerce, and integrated shopping channels has changed how consumers interact with businesses, making customer experience quality an important factor in maintaining competitiveness and customer loyalty. Therefore, this study aims to analyze the influence of omnichannel strategy and personal selling on customer experience quality among SME consumers in Cirebon City. This research employed a quantitative approach using survey data collected from 180 respondents who had experience purchasing from retail SMEs in Cirebon City. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine the relationships between variables. The findings reveal that omnichannel strategy has a positive and significant effect on customer experience quality by providing seamless channel integration, easier access to information, and consistent service interactions. In addition, personal selling also significantly improves customer experience through effective communication, empathy, and responsive customer service. Simultaneously, both variables strongly influence customer experience quality. In conclusion, the integration of omnichannel strategies and effective personal selling can help SMEs create more satisfying, consistent, and sustainable customer experiences in the digital business environment.